Sosialisasi Ilustrasi, Inspirasi Dan Visualisasi Master Plan Menggunakan Software Autocad (2D) Dan Sketchup (3D) Kepada Staff Kantor Lurah Kelurahan Sekijang, Pelalawan - Audi Salsabila Nur Rizki; Deby Ayunda Syahira; Lily Andreani; Muhammad Reza Alfath; M. Ulin Nuha; Nadira Dwi Cahya Rinia; Nur Astri Nadira; Syafira Anjani; Tazki Azzikra; Vioni Sasmia (Universitas 17 Agustus 1945 Semarang, 2023)
In order to develop the economic center, Sekijang Village is making efforts to ensure the smooth progress of the development with crucial steps, one of which is the visual planning of the construction. This is done to anticipate potential losses effectively. However, we are aware that the community's knowledge regarding the utilization of technology in building design is still quite limited. Therefore, as a form of community service, the students of the Real Work Class program from the University of Riau in 2023 are implementing a socialization program with the aim of introducing the use of AutoCAD and SketchUp software. Additionally, the students are also presenting the master plan visualization for Sekijang Village, currently being developed by the KKN UNRI students, with the goal of assisting in designing a better economic center for Sekijang Village in the coming years